11-(7×5-9×9÷f÷3)÷8=7
Răspunsuri la întrebare
Răspuns de
5
11 - (7 · 5 - 9 · 9 ÷ f ÷ 3) ÷ 8 = 7
11 - (35 - 81 ÷ f ÷ 3) ÷ 8 = 7
(35 - 81 ÷ f ÷ 3) ÷ 8 = 11 - 7 = 4
35 - 81 ÷ f ÷ 3 = 4 · 8 = 32
81 ÷ f ÷ 3 = 35 - 32 = 3
81 ÷ f = 3 · 3 = 9
f = 81 : 9
f = 9
//
11 - (35 - 81 ÷ f ÷ 3) ÷ 8 = 7
(35 - 81 ÷ f ÷ 3) ÷ 8 = 11 - 7 = 4
35 - 81 ÷ f ÷ 3 = 4 · 8 = 32
81 ÷ f ÷ 3 = 35 - 32 = 3
81 ÷ f = 3 · 3 = 9
f = 81 : 9
f = 9
//
Alte întrebări interesante
Fizică,
9 ani în urmă
Franceza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Germana,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă